Sub‐Nanometer Mono‐Layered Metal–Organic Frameworks Nanosheets for Simulated Flue Gas Photoreduction - He, Dong; Wang, Qian; Rong, Yan; Xin, Zhifeng; Liu, Jing‐Jing; Li, Qiang; Shen, Kejing; Chen, Yifa (Advanced materials (Weinheim), 2024)
The dilemma between the thickness and accessible active site triggers the design of porous crystalline materials with mono‐layered structure for advanced photo‐catalysis applications. Here, a kind of sub‐nanometer mono‐layered nanosheets (Co‐MOF MNSs) through the exfoliation of specifically designed Co3 cluster‐based metal–organic frameworks (MOFs) is reported. The sub‐nanometer thickness and inherent light‐sensitivity endow Co‐MOF MNSs with fully exposed Janus Co3 sites that can selectively photo‐reduce CO2 into formic acid under simulated flue gas. Notably, the production efficiency of formic acid by Co‐MOF MNSs (0.85 mmol g−1 h−1) is ≈13 times higher than that of the bulk counterpart (0.065 mmol g−1 h−1) under a simulated flue gas atmosphere, which is the highest in reported works up to date. Theoretical calculations prove that the exposed Janus Co3 sites with simultaneously available sites possess higher activity when compared with single Co site, validating the importance of mono‐layered nanosheet morphology. These results may facilitate the development of functional nanosheet materials for CO2 photo‐reduction in potential flue gas treatment. A kind of sub‐nanometer mono‐layered nanosheets (Co‐MOF MNSs) is successfully prepared with remarkable performance in selective CO2 photo‐reduction into formic acid under simulated flue gas.